2007
DOI: 10.1007/bf03262586
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic eruption of first permanent molars: A preliminary report of presenting features and associations

Abstract: This study, the first in a British population, has identified a significant association between ectopic eruption of first permanent molars and other dental anomalies. A multifactorial aetiology is thus supported and clinicians should be alert to the co-existence of ectopic eruption and other dental anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 9 publications
4
34
2
Order By: Relevance
“…Although the prevalence of dental caries has been slowly declining in many developed countries, this disease continues to be a major public health problem in industrialised countries and has become an emerging public health problem in developing countries [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Although the prevalence of dental caries has been slowly declining in many developed countries, this disease continues to be a major public health problem in industrialised countries and has become an emerging public health problem in developing countries [1]. …”
Section: Introductionmentioning
confidence: 99%
“…There is a wide spectrum of dental anomalies but they broadly encompass deviations of tooth number, morphology, structure, position, or eruption. Furthermore, the presence of one anomaly should always alert clinicians to the possibility of others, as numerous studies have demonstrated significant inter‐relationships between certain anomaly types . Notably, a study of almost 5000 Italian children, aged 7‐14 years, revealed significant reciprocal relationships between missing second premolars, enamel hypoplasia, diminutive maxillary lateral incisors, palatally displaced maxillary canines, and primary molar infra‐occlusion .…”
Section: Introductionmentioning
confidence: 99%
“…According to Italian Ministerial Guidelines [22, 23], it is recommended to encourage breastfeeding, in order to promote more normal jaw development. In fact, proper labial and lingual posture, adequate nasal breathing, and correct transverse diameter of the palate are related to natural breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial feeding may promote malocclusion, when combined with non-nutritive sucking or with rhinitis; in fact, bottle-fed children can develop sucking habits more frequently than others. Non-nutritive sucking, together with allergic rhinitis, seems to be the most important factor for the development of a posterior crossbite in children under 5 years [22, 23]. It is also recommended to discourage non-nutritive sucking at 2 years of age, in order to definitively stop the habit by 3 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation